A new species of Pleurothallis (Pleurothallidinae, Orchidaceae) from the historic sanctuary of Machupicchu, Perú - Alexander Damián-Parizaca; Marco Federico Monteros; Daxs Coayla Rimachi; Joseph Walston; Nicole Mitidieri-Rivera (PhytoKeys)
Pleurothallis machupicchuensis, a new species from Cusco, Perú, is described and illustrated. Information regarding its distribution, habitat, and phenology is provided. Morphologically, P. machupicchuensis closely resembles P. scurrula and P. sannio but can be distinguished mainly by the morphology of the lip. The new species features an ovate, obtuse lip with a prominent bilobed, reniform glenion, in contrast to the oblong-ovate, acute lip with a small rounded glenion observed in P. scurrula, and the ovate, rounded lip with an oblong glenion in P. sannio.